FEATURES OF MARKETING ACTIVITIES AND THE IMPACT OF ITS DEVELOPMENT ON AGROLOGISTICS SERVICES - Karimova Maftuna Nurdinovna; Islamov Farxod Raxmatullaevich (Journals Park Publishing, 2023)
The article explores the theoretical aspects of the terms “agricultural marketing”, “agricultural marketing” as one of the components of marketing. The purpose of this article is to identify and analyze the main features of the use of marketing by agricultural enterprises and impact of agricultural marketing on agrologistics services. It has been revealed that the distinctive characteristics of agricultural marketing are: the dependence of the volume of agricultural production on natural and climatic conditions, the importance of the product for consumers in terms of food security, the seasonality of agricultural production, the existence of enterprises of various forms of ownership and management in the agricultural production system, different levels of marketing activities, imperfection of the regulatory framework in the field of regulation of marketing activities. Taking into account the identified features, a model was developed that covers not only agricultural policy, but also agrologistic and agricultural marketing. Circumstances have been established that make it possible to improve the marketing activities of agrologistics services.
Keywords: Marketing, agriculture, agrologistics services, enterprise, agromarketing.